Pengembangan Pembelajaran Berbasis Contextual Teaching and Learning pada Mata Pelajaran PAI dalam Membentuk Karakter Siswa Kelas 3 SDN 5 Rasau Jaya - Nurhafifah Tri Nugroho (Jurnal Kependidikan, 2021)
The purpose of this research is to analyze the development of Contextual Teaching and Learning (CTL) based learning in shaping student character. This research uses a development approach. Based on the results of research, this Contextual Teaching and Learning (CTL) strategy is a strategy that involves many learners by associating the material with real-life contexts. The Contextual Teaching and Learning (CTL) model accommodates the involvement of students physically as well as mentally. The development variation in the use of character-charged Contextual Teaching and Learning (CTL) strategies is the application of CTL which does not need to change the content of the discussion, but rather relates what is in learning with real life. So contextual teaching and learning (CTL) is very appropriate to be used in shaping student character, especially in pai (Islamic religious education) subjects. Keywords: Contextual Teaching and Learning (CTL), PAI, Character ABSTRAK Tujuan penelitian ini untuk menganalisis pengembangan pembelajaran berbasis Contextual Teaching and Learning (CTL) dalam membentuk Karakter siswa. Penelitian ini menggunakan pendekatan pengembangan. Berdasarkan dari hasil penelitian, strategi Contextual Teaching and Learning (CTL) ini merupakan strategi yang banyak melibatkan peserta didik dengan mengaitkan materi dengan konteks kehidupan nyata. Model Contextual Teaching and Learning (CTL) mengakomodasikan keterlibatan peserta didik secara fisik maupun mental. Variasi pengembangan dalam penggunaan strategi Contextual Teaching and Learning (CTL) bermuatan karakter adalah penerapan CTL yang mana tidak perlu merubah isi pembahasan, melainkan mengaitkan apa yang ada dalam pembelajaran dengan kehidupan nyata. Sehingga Contextual Teaching and Learning (CTL) ini sangat tepat untuk digunakan dalam membentuk Karakter Siswa, khususnya dalam mata pelajaran PAI (Pendidikan Agama Islam). Kata Kunci: Contextual Teaching and Learning (CTL), PAI, Karakter